The Influence of Work Discipline and Work Environment on Employee Performance in the Social Service Office of Palu City Indonesia - Abd. Rahman; Ruby Santamoko; Muhammad Umar; Soegeng Wahyoedi (Annals of Human Resource Management Research, 2026)
Purpose: This study aimed to examine the effects of work discipline and work environment on employee performance at the Social Service Office of Palu City. Improving employee performance in public sector institutions is essential for ensuring effective public service delivery and organizational productivity. Research Methodology: This study used a quantitative survey approach involving 45 employees at the Palu City Social Service Office as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25 to determine the influence of work discipline and work environment on employee performance. Results: The results indicate that work discipline and work environment positively and significantly affect employee performance. Partially, work discipline shows a significant influence on employee performance (β = 0.421; p < 0.05), while the work environment also has a significant positive effect (β = 0.387; p < 0.05). Simultaneously, both variables significantly affected employee performance, with an R² value of 0.62, indicating that 62% of the variation in employee performance could be explained by work discipline and work environment. Conclusions: The study concludes that improving work discipline and creating a supportive work environment can significantly enhance employee performance in public-sector organizations. Limitations: This study was limited by its cross-sectional design and relatively small sample size. Contributions: This study contributes to the development of public administration and human resource management literature, particularly in understanding the factors influencing employee performance in local government institutions.